Sinergi Paramassa: Implementation of the Social Values of the Meugang Tradition into Digital Music Composition - Gusmanto, Rico; Denada, Berlian (Gondang: Jurnal Seni dan Budaya, 2023)
The Meugang tradition as Acehnese local wisdom is an activity that has a togetherness. This togetherness is a social value that creates a harmonious society in the midst of the globalization era. This is something interesting to implement in the form of music compositions. The aim of this research is to create a music that implement social values in the Meugang tradition through the use of a Digital Audio Workstation. The method used is an artistic research method which consists of 1) the formulation of ideas; 2) determine the work; 3) express ideas; 4) and performances. The result of this research is music entitled "Sinergi Paramassa". This music consists of two parts that represent Meugang activities and values asah, asih, and asuh. It is hoped that this research can be an answer to the challenges of music development in the digital era in terms of the novelty of the music content sourced from local Indonesian wisdom.